Analysis of Ruthenium(III) in Micro Amounts by Kinetic Method - Chimatadar, S.A.; Madawale, S.V.; Nandibewoor, S.T. (Asian Journal of Chemistry, 2016)
Ruthenium(III) catalyzed oxidation of As(III) by Ce(IV) in acid solution has been utilized to develop a kinetic method for the analysis of ruthenium(III) in the range of 0.04–0.065 μg cm–3 by spectrophotometric technique. Interferences of various ions were also studied.